Inter-vortex forward Brillouin scattering by chiral phonons - Zeng, Xinglin; Russell, Philip St J.; Stiller, Birgit (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Forward Brillouin scattering (FBS) in optical fibres, in which co-propagating optical modes are coupled by acoustic modes, provides a powerful and flexible mechanism for controlling the structure and frequency of light fields, with applications in, e.g., high harmonic mode-locked fibre lasers [1] and optical sensing [2]. Here we report the observation of seeded inter-vortex Brillouin scattering in a three-fold rotationally symmetric photonic crystal fibre (PCF) [3], mediated by a rotating higher order flexural acoustic mode, sometimes known as a "screw mode" [4].
CRIS-Team Scopus Importer:2024-12-16